The Effect of Scientific Approach and Interpersonal Interaction of Islamic Education to Student Characters in Integrated Islamic School Al Hafiz Langkat District - Amiruddin Siahaan; Hafsah Hafsah; Satria Mandala (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this research are to find out: (1) the scientific approach has a significant influence on student character, (2) interpersonal interaction has a significant effect on student character, and (3) the effect of scientific approach and interpersonal interaction together on student character. The research method used was quasi experiment with 2 x 2 factorial designs. The sampling technique used was cluster random sampling. Data collection instruments are questionnaires and tests. Data analysis technique used two-way analysis of variance. The research findings show: (1) there is a positive and significant influence between the scientific learning approach and student character, (2) there is a positive and significant effect between interpersonal interactions in the learning of Islamic Education with student character, and (3) there is a positive and significant effect between scientific approach and interpersonal interaction on learning Islamic Education with student character.